1995
DOI: 10.21273/jashs.120.6.938
|View full text |Cite
|
Sign up to set email alerts
|

Improved Shoot-tip Micropropagation of Pistacia Vera L. and the Beneficial Effects of Methyl Jasmonate

Abstract: Micropropagation of Pistacia vera `Mateur' was improved by adding MeJA to the multiplication and rooting media. Shoot-tip cultures established from grafted trees were maintained on a modified Murashige and Skoog medium containing 5 μm BA and 0.05 μm IBA. Adding 0.3, 1, or 3.2 μm MeJA improved shoot multiplication rates 2.5, 3.0, and 2.3, respectively. There was a significant interaction between the effects of auxin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…As a result of their experiments on rooting 2-3 cm long shoot tips obtained by the micropropagation of shoots grown in vitro from mature seeds of Pistacia khinjuk, a rootstock of pistachio, Tilkat et al (2005) reported that the best results, with a 100% rooting rate, were obtained from explants cultured in the MS medium containing 0.5 mg l -1 IBA. Dolcet-Sanjuan and Claveria (1995) had reported that in their study on the micropropagation of 3-year-old P. paleastina rootstock shoot tips, root formation occurred in 62% of 1-3 cm long shoots cultured in a medium containing 6.0 mg l -1 NAA. When previous studies were evaluated, in contrast with the results of Dolcet-Sanjuan and Claveria (1995), parallel with the results reported by Martinelli (1988), Barghchi and Alderson (1989), Parfitt and Almehdi (1994), Onay (2000) and Onay et al (2003), among all the auxin types (IBA, IAA, NAA and 2,4-D tested for in vitro rooting of shoots taken from pistachio trees), the most satisfactory auxin and its concentration were IBA and 2.0 mg l -1 , respectively, with 2 cm long shoots, giving a 65% rooting rate.…”
Section: Effects Of Shoot Length On Rootingmentioning
confidence: 99%
“…As a result of their experiments on rooting 2-3 cm long shoot tips obtained by the micropropagation of shoots grown in vitro from mature seeds of Pistacia khinjuk, a rootstock of pistachio, Tilkat et al (2005) reported that the best results, with a 100% rooting rate, were obtained from explants cultured in the MS medium containing 0.5 mg l -1 IBA. Dolcet-Sanjuan and Claveria (1995) had reported that in their study on the micropropagation of 3-year-old P. paleastina rootstock shoot tips, root formation occurred in 62% of 1-3 cm long shoots cultured in a medium containing 6.0 mg l -1 NAA. When previous studies were evaluated, in contrast with the results of Dolcet-Sanjuan and Claveria (1995), parallel with the results reported by Martinelli (1988), Barghchi and Alderson (1989), Parfitt and Almehdi (1994), Onay (2000) and Onay et al (2003), among all the auxin types (IBA, IAA, NAA and 2,4-D tested for in vitro rooting of shoots taken from pistachio trees), the most satisfactory auxin and its concentration were IBA and 2.0 mg l -1 , respectively, with 2 cm long shoots, giving a 65% rooting rate.…”
Section: Effects Of Shoot Length On Rootingmentioning
confidence: 99%
“…However, the use of these standard media increases the cost of micropropagation of Pistacia sp . due to the appearance of physiological disorders, such as shoot tip necrosis (STN), hyperhydricity or the formation of callus (BC) at the base of the shoots (Abousalim and Mantell, 1992, 1994; Dolcet-Sanjuan and Claveria, 1995; Onay, 1996). …”
Section: Introductionmentioning
confidence: 99%
“…To avoid those problems, different alternatives have been suggested, based mainly on the combination of macro-, micro-elements and/or vitamins previously proposed for improving the effectiveness of the multiplication of shoots (Onay, 2000; Tilkat et al, 2005, 2008; Benmahioul et al, 2012), or on the incorporation of additional ingredients to the basal culture media, such as calcium gluconate, silver nitrate, ascorbic acid or vanillin, among others (Abousalim and Mantell, 1992, 1994; Parfitt and Almehdi, 1994; Dolcet-Sanjuan and Claveria, 1995; Mederos-Molina and Trujillo, 1999; Akdemir et al, 2012; Kilinç et al, 2015; Marín et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…There has been some success in establishment of mature pistachios by direct organogenesis (Yang & Lüdders, 1993;Dolcet-Sanjuan & Claveria, 1995;Onay, 2000) and somatic embryogenesis (Onay et al, 1995(Onay et al, , 1996(Onay et al, , 1997Onay et al, 2004a). Onay (2000) harvested 3-4 cm long terminal lignified stem sections from 30-year-old pistachio trees and immersed the cut ends in plant growth regulator solutions, before placing them in a greenhouse medium.…”
Section: Introductionmentioning
confidence: 99%